NGFS climate scenarios for the euro area: Role of fiscal and monetary policy conduct: Opening up the macroeconomic toolbox and its sensitivity to policy settings - Matthieu Darracq Pariès; Stéphane Dées; Annabelle De Gaye; Laura Parisi; Yiqiao Sun (European Central Bank (ECB), 2023)
In this paper we analyse the sensitivity of the macroeconomic outcomes under the Network for Greening the Financial System's (NGFS's) Phase III net-zero and delayed transition scenarios to different monetary and fiscal policy settings. In doing so, we provide a rare application of the NGFS climate scenarios to economic assessment through the lens of the macroeconomic modelling frameworks underlying the scenario construction (e.g. NiGEM). Using the model to disentangle the main drivers of the scenarios, we show that gross domestic product (GDP) growth is shaped by physical and transition shocks jointly, whereas transition shocks account for most of the inflationary pressure. As regards alternative policy settings within the model, it turns out that Fiscal recycling options become more discriminant in terms of GDP impact in the medium term. Full recycling through government investment yields the strongest output multiplier, whereas recycling through household transfers or reduced income taxes yields the lowest multiplier. During the transition, euro area macroeconomic variables respond very similarly if two-pillar or price level-targeting monetary policy rules are followed. The Taylor- rule, reacting to inflation and output gap, yields higher and more persistent inflation as well as stronger short-term interest rate increases. These findings are certainly modelspecific but do reflect the policy sensitivity embedded of the NGFS scenarios, within the confines of the very model used to build them up.
Keywords: Q54; E3; E6; D6; 330; climate scenarios; modelling strategy; monetary policy; fiscal policy